Development of Hygiene and Sanitation Evaluation of Poultry Slaughter in Traditional Markets - Mohamed Arif; Saifuddin; Mochamad Lutfan Hafidullah; Ridho Muhammad Rizqi; Moh. Khoirul Anam (Asosiasi Ahli Administrasi Indonesia, 2025)
Traditional markets remain the main distribution center for poultry products in Indonesia, but hygiene and sanitation practices in poultry slaughterhouses often do not meet food safety standards. Inadequate environmental conditions, workers' inattention to hygiene, and the lack of sanitation facilities increase the risk of cross-contamination, which can threaten public health. This study aims to develop a simple, applicable, and technical indicator-based evaluation tool to assess the hygiene and sanitation conditions of poultry slaughterhouses in traditional markets, while identifying key problems that occur in the field. The research method used is a qualitative descriptive method with a field study approach. Data were collected through direct observation, in-depth interviews, and visual documentation at several poultry slaughterhouses in the traditional markets used as research locations. The evaluation instrument was developed based on physical environmental indicators, worker behavior, and waste management systems, which were then tested to measure its effectiveness in identifying actual problems. The results show that the majority of poultry slaughterhouses in traditional markets still face significant challenges in terms of hygiene and sanitation. Basic infrastructure such as drainage, clean water supply, and handwashing facilities are very limited. Worker behavior in maintaining personal hygiene and work equipment is also still low. These findings underscore the need for training-based interventions and facility improvements, as well as the development of a continuous monitoring system to maintain better hygiene and sanitation standards in traditional markets. The developed evaluation instrument proved effective as a practical tool for identifying weaknesses and designing more targeted and sustainable improvement.